Work from Home and Work-Family Conflict: A Systematic Literature Review of Empirical Studies Since the COVID-19 Pandemic : [Kerja dari Rumah dan Konflik Pekerjaan–Keluarga: Tinjauan Literatur Sistematis terhadap Studi Empiris sejak Pandemi COVID-19] - Laila Listiana Ulya; Azzahra Putri Khairunnisa; Amira Rosyida Arisya'bani; Enindya Zen Akalili (Universitas Pelita Harapan, 2026)
Working from home (WFH) has now become a permanent working model in various organisations in the wake of the COVID-19 pandemic, but this change has also given rise to new challenges related to the balance between work and family roles. This phenomenon is closely related to work–family conflict (WFC), which can impact employee well-being and performance. On the other hand, although WFH is often associated with flexibility and the convenience of working from home, this practice also has negative consequences due to the blurring of boundaries between work and domestic life. This study aims to systematically review the relationship between WFH and WFC to answer the question of whether WFH truly provides beneficial flexibility or or instead increases role conflict within the family domain. This study employs a Systematic Literature Review (SLR) method on 15 empirical articles published between 2023 and 2025, which were collected through a literature search conducted from October to November 2025 using the Google Scholar database. The results of the SLR indicate that WFH tends to increase WFC, with determining factors such as digital pressure, work demands, family roles, and gender differences. These findings suggest that although WFH offers flexibility, its implementation without clear boundary management may intensify role conflict. This study is expected to provide insights into organizations and workers regarding the strategies and policies needed to minimise WFC in the implementation of WFH. Abstrak Bahasa Indonesia: Work from home (WFH) kini menjadi salah satu model kerja permanen dalam berbagai organisasi pasca pandemi COVID-19, namun perubahan ini juga memunculkan tantangan baru terkait keseimbangan peran antara pekerjaan dan keluarga. Fenomena tersebut berkaitan erat dengan work–family conflict (WFC) yang dapat berdampak pada kesejahteraan serta kinerja pekerja. Di sisi lain, meskipun WFH sering diasosiasikan dengan fleksibilitas dan kemudahan bekerja dari rumah, praktik ini juga menimbulkan konsekuensi negatif akibat kaburnya batas antara ranah pekerjaan dan kehidupan domestik. Penelitian ini bertujuan untuk meninjau secara sistematis hubungan antara WFH dan WFC guna menjawab pertanyaan apakah WFH benar-benar memberikan fleksibilitas yang menguntungkan atau justru meningkatkan konflik peran keluarga. Penelitian ini menggunakan metode Systematic Literature Review (SLR) terhadap 15 artikel empiris yang dipublikasikan pada periode 2023–2025, yang dikumpulkan melalui pencarian literatur pada Oktober–November 2025 menggunakan basis data Google Scholar. Hasil SLR menunjukkan bahwa WFH cenderung meningkatkan WFC, dengan faktor penentu seperti tekanan digital, tuntutan kerja, peran keluarga, dan perbedaan gender. Temuan ini mengindikasikan bahwa meskipun WFH menawarkan fleksibilitas, implementasinya tanpa pengelolaan batas kerja yang jelas justru berpotensi memperbesar konflik peran. Penelitian ini diharapkan dapat memberikan wawasan bagi organisasi dan pekerja mengenai strategi dan kebijakan yang dibutuhkan untuk meminimalkan WFC pada pelaksanaan WFH.